Comparative study of mountain sickness - Cuba Caparó, Alberto (1956)
In order to make a comparative study of Mountain Sickness affecting humans and cattle and sheep has been reviewed briefly the clinical, hematologic and pathologic aspects found in the literature. The anatomic correlation of clinical symptoms and major injuries in the bovine and ovine, emphasizing, among other things, the similarity of symptoms and lesions observed in the myocardium and the adrenal cortex does. Mountain Sickness In the three species considered in this study polycythemia is one of the most important manifestations. However. emphasizes that the normal height ram no modifications CBC as those seen in man and in normal cattle. The hipotocoferolemia is noted as a factor that may explain the transient polycythemia has been observed in normal lambs and is associated with myocardial lesions observed in the Mountain Sickness affecting this species. Hypertrophy and hyperplasia of the adrenal cortex in the syndrome of adaptation to high altitude and severe injuries of the same as an explanation for the progressive and fatal outcome in some cases of Mountain Sickness in cattle and sheep is noted.